AB0600 High Prevalence of Reduced Bone Mineral Density and Undertreatment of Osteoporosis in Patients with Systemic Sclerosis. (15th July 2016) - Spanjer, M.J.; Voskuyl, A.E.; Lems, W.F.; Bultink, I.E.M.
Abstract : Background: Systemic sclerosis is a systemic inflammatory rheumatic disease with a very low prevalence, that has been associated with an increased risk of low bone mineral density (BMD) 1, but data on risk factors associated with bone loss in systemic sclerosis are scarce. Objectives: The objective of this study was to investigate the prevalence of and risk factors for low BMD in patients with systemic sclerosis. Methods: Demographic and clinical data of 61 patients with systemic sclerosis were collected. BMD measurements of the lumbar spine, total hip and femoral neck were performed using DXA. Osteoporosis was defined as a T score less than -2.5 SD and osteopenia as a T-score between -1.0 and -2.5 SD, according to WHO definitions. Systemic sclerosis disease severity was defined by the Rodnan skin score and by the Medsger disease severity score 2 . Multiple linear regression analyses was used to assess factors associated with BMD. Results: Patients were on average 56.7±12.4 years old and 72% were female of whom 77% postmenopausal. BMD measurements revealed osteopenia or osteoporosis in at least one measurement site in 67% of the patients, of whom 30% had osteoporosis. Low body mass index and postmenopausal state were significantly associated with low BMD in all skeletal sites. No significant associations were found between age, Rodnan skin score, Medsger disease severity score, glucocorticoid treatment and BMD. Of the 30% of patients who had an indication for anti-osteoporosis treatment, 91% did not receive anti-osteoporosis medication. Conclusions: The results of this cross-sectional study demonstrate a high frequency of osteoporosis or osteopenia in 67% of our patients with systemic sclerosis and low body mass index and postmenopausal state were identified as the most important risk factors. No relationship between disease severity and BMD was found, which could be related to the sample size, although it can be argued that low BMI is, at least partly, a marker of disease severity. This study also shows a high frequency (91%) of undertreatment of osteoporosis in this patient group. These results underline the importance of monitoring and treatment of low BMD in systemic sclerosis. References: Omair MA, et al. Low bone density in systemic sclerosis: a systematic review. J Rheumatol 2013;40:1881–90. Medsger TA jr, et al. Assessment of disease severity and prognosis. Clin Exp Rheumatol 2003;21:S42–6. Disclosure of Interest: None declared